Between Soup and Soap: Iconic Nationality, Mass Media and Pop Culture in Contemporary Lithuania - Tereškinas, Artūras (Sociologija. Mintis ir veiksmas, 1999)
This article aims to theorize the complex relationship between the sublimity of Lithuanian national identity and its everyday happenings by playing with national significations and resignifications extracted from a wide array of texts written in the nineteenth century and in the 90s of the twentieth century. Mass media, pop culture and the everyday are understood as spaces of a new nationness in practice demonstrating how the national imaginary is constructed and deconstructed through the circulation of televisual and print media images. Drawing on the ideas of Benedict Anderson about imagined communities created by the press, the article touches upon the various kinds of media producing, in Anderson's words, a "league of anonymous equals." How does media help the Lithuanian people think the nation? How do the people negotiate their desire for belongings and solidarities through their everyday acts and experiences of national imaginary?
Keywords: nationness; mass-media; pop culture; iconic nationality; Benedict Anderson; imagined community